ANALYSIS OF INCREASING MSME EMPOWERMENT THROUGH GOVERNMENT SERVICES: THE JAKPRENENUR PROGRAM IN EAST JAKARTA - Rahardjo, Budi; Rustanto, Agung Edi (Universitas Padjadjaran, 2024)
This research investigates the impact of service facilitation actions through the Jakpreneur Program on MSME empowerment. However, challenges arise in ensuring consistent program implementation and measuring sustainable empowerment outcomes. Many MSMEs struggle to utilize available resources fully, and the existing service mechanisms often fall short of addressing their specific needs, particularly in areas like financial literacy and market access. Using an action research method, this study collects data through questionnaires, interviews, observations, and document analysis to explore these issues. Technical data analysis was carried out using the N-Gain test, testing the pre-test and post-test results of the actions carried out in this study. Collaboration with the Sub-Department of Industry, Trade, Cooperatives, and MSMEs enables an in-depth understanding of both MSMEs and program facilitators’ perspectives. Jakpreneur’s services include registration, training, mentoring, licensing, marketing, financial reporting, and capital assistance. The findings indicate increased MSME empowerment across six dimensions: entrepreneurial development, human resource quality, poverty reduction, entrepreneurial resilience, productivity and competitiveness, and policy support. This study provides information on the effectiveness of MSME service delivery by identifying gaps between before and after the implementation of services that positively impact the development of MSME businesses in Jakarta. Penelitian ini mengkaji dampak tindakan fasilitasi layanan melalui Program Jakpreneur terhadap pemberdayaan UMKM. Namun, tantangan muncul dalam memastikan implementasi program yang konsisten dan mengukur hasil pemberdayaan yang berkelanjutan. Banyak UMKM yang kesulitan memanfaatkan sumber daya yang tersedia secara penuh, dan mekanisme layanan yang ada sering kali tidak mampu memenuhi kebutuhan spesifik mereka, khususnya di bidang seperti literasi keuangan dan akses pasar. Dengan menggunakan metode penelitian tindakan, penelitian ini mengumpulkan data melalui kuesioner, wawancara, observasi, dan analisis dokumen untuk mengeksplorasi isu-isu tersebut. Teknis analisis data dilakukan dengan uji N-Gain, menguji hasil pre test dan post test dari Tindakan yang dilakukan pada penelitian ini. Kolaborasi dengan Sub-Dinas Perindustrian, Perdagangan, Koperasi, dan UMKM memungkinkan pemahaman yang mendalam tentang perspektif UMKM dan fasilitator program. Layanan Jakpreneur meliputi pendaftaran (P1), pelatihan (P2), pendampingan (P3), perizinan (P4), pemasaran (P5), pelaporan keuangan (P6), dan permodalan (P7). Hasil penelitian menunjukkan peningkatan pemberdayaan UMKM di enam dimensi: pengembangan kewirausahaan, kualitas sumber daya manusia, penanggulangan kemiskinan, ketahanan kewirausahaan, produktivitas dan daya saing, dan dukungan kebijakan. Studi ini berkontribusi memberikan informasi efektivitas penyampaian layanan UMKM dengan mengidentifikasi kesenjangan antara sebelum dan sesudah implementasi pelayanan yang memberikan dampak positif bagi perkembangan usaha UMKM di Jakarta.